Distribution of oligochaetes in a stream in the Atlantic Forest in southeastern Brazil - BFJV. Rosa; RT. Martins; RG. Alves (Brazilian Journal of Biology)
The oligochaetes are considered good indicators of ecological conditions and specific types of habitats. Among the factors that influence the distribution of these invertebrates are the water flow and the nature of the substrate. The aim of this study is to describe the composition and distribution of oligochaete species in a first-order stream in Atlantic Forest and try to identify if some species are associated with characteristics of particular types of habitats. In the dry season and in the rainy season, sand and litter samples in two riffle areas and two pool areas were collected in different parts along the stream using a hand net. The greatest observed richness and abundance occurred in sand in the pool, however the greatest estimated richness was obtained for litter in the pool. The Kruskal-Wallis analysis showed effect of the different types of habitat on the abundance and richness of oligochaetes. The Nonmetric Multidimensional Scaling (NMDS) and Multiresponse Permutation Procedure analysis (MRPP) indicated that the variation in the fauna composition had relation with different types of substrates. The indicator species analysis showed that Limnodrilus. hoffmeisteri was an indicator species in both the riffle sand and pool sand and Pristina americana was only an indicator in the pool sand. The high organic matter content in both sandy habitats probably favored the greater abundance of oligochaetes. The results showed that the substrate constitutes an important factor for the local distribution of these invertebrates in streams. The variation of the community structure among mesohabitats and the presence of indicator species of specific types of habitats in the stream demonstrate the importance of environmental heterogeneity for the oligochaetes fauna in forested streams.